Genetics of blood lipids among 300, 000 multi-ethnic participants of the Million Veteran Program. (November 2018) - Klarin, Derek; Damrauer, Scott; Cho, Kelly; Sun, Yan; Teslovich, Tanya; Honerlaw, Jacqueline; Gagnon, David; DuVall, Scott; Li, Jin; Peloso, Gina; Chaffin, Mark; Small, Aeron; et al.
Abstract The Million Veteran Program (MVP) was established in 2011 as a national research initiative to determine how genetic variation influences the health of US military veterans. Here we genotyped 312, 571 MVP participants using a custom biobank array and linked the genetic data to laboratory and clinical phenotypes extracted from electronic health records covering a median of 10.0 years of follow-up. Among 297, 626 veterans with at least one blood lipid measurement, including 57, 332 black and 24, 743 Hispanic participants, we tested up to around 32 million variants for association with lipid levels and identified 118 novel genome-wide significant loci after meta-analysis with data from the Global Lipids Genetics Consortium (totaln > 600, 000). Through a focus on mutations predicted to result in a loss of gene function and a phenome-wide association study, we propose novel indications for pharmaceutical inhibitors targeting PCSK9 (abdominal aortic aneurysm), ANGPTL4 (type 2 diabetes) and PDE3B (triglycerides and coronary disease). Analysis of genetic data and blood lipid measurements from over 300, 000 participants in the Million Veteran Program identifies new associations for blood lipid traits.